2021
DOI: 10.1186/s41983-021-00289-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in central nervous system disorders: current advances in pathogenesis and treatment

Abstract: MicroRNAs (miRNAs) are a class of short, non-coding, regulatory RNA molecules that function as post transcriptional regulators of gene expression. Altered expression of multiple miRNAs was found to be extensively involved in the pathogenesis of different neurological disorders including Alzheimer’s disease, Parkinson’s disease, stroke, epilepsy, multiple sclerosis, amyotrophic lateral sclerosis, and Huntington’s disease. miRNAs are implicated in the pathogenesis of excitotoxicity, apoptosis, oxidative stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…miRNAs have been described to be implicated in different processes such as inflammation, neurogenesis, apoptosis, blood-brain barrier protection and/or remyelination [33,34]. The deregulation of their levels in patients with neurological diseases might represent new potential biomarkers as well as new avenues for research in developing new therapies [33][34][35]. Some of the unsolved challenges in miRNA profiling studies include the existence of heterogeneous and conflicting results as well as the lack of replication among studies [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have been described to be implicated in different processes such as inflammation, neurogenesis, apoptosis, blood-brain barrier protection and/or remyelination [33,34]. The deregulation of their levels in patients with neurological diseases might represent new potential biomarkers as well as new avenues for research in developing new therapies [33][34][35]. Some of the unsolved challenges in miRNA profiling studies include the existence of heterogeneous and conflicting results as well as the lack of replication among studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, circulating miRNA profiles have been widely studied in different conditions to exploit their potential as biomarkers. miRNAs have been described to be implicated in different processes such as inflammation, neurogenesis, apoptosis, blood–brain barrier protection and/or remyelination [ 33 , 34 ]. The deregulation of their levels in patients with neurological diseases might represent new potential biomarkers as well as new avenues for research in developing new therapies [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…46 and miR-411 47 could lessen inflammatory responses in animals with SCI. 48 Other research has demonstrated that miR-146a is involved in the control of inflammation and the innate immune system. 49 Its deregulation in a variety of diseases and pathological processes associated with inflammation, particularly in the nervous system, suggests its significant role in neurodegenerative diseases, particularly neuroinflammation.…”
Section: Inflammationmentioning
confidence: 99%
“…Most miRNAs are involved in the regulation of fundamental biological processes, such as proliferation (Lenkala et al, 2014), differentiation (Yao, 2016), inflammation (Zhou W. et al, 2018), apoptosis (Taghavipour et al, 2020), cell cycle (Mens and Ghanbari, 2018), and immune response (Chandan et al, 2020). Due to their wide range of functions, miRNA dysregulation has significant consequences in terms of cellular outcomes enhancing the development of a wide range of diseases, including cardiovascular diseases (Zhou S.-S. et al, 2018), neurological disorders (Hussein and Magdy, 2021), autoimmune disorders (Salvi et al, 2019) and cancer (Peng and Croce, 2016).…”
Section: Mirnas and Cancermentioning
confidence: 99%